2017
DOI: 10.1371/journal.pone.0172406
|View full text |Cite
|
Sign up to set email alerts
|

Diet diversity and nutritional status among adults in southwest China

Abstract: BackgroundWith rapid urbanization in the past decades, diet diversity continues to increase in China. The present cross-sectional study aims to explore the association between dietary diversity and nutritional status among adults in southwest China.MethodsThis study used data from 2011–2012 National Nutritional Survey in Yunnan Province, southwest China (N = 1105).Data of three consecutive 24-hour dietary recalls were used to calculate dietary diversity scores (DDS) and nutrient adequacy ratio (NAR). Body mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
51
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 36 publications
14
51
4
Order By: Relevance
“…The amount of dietary sodium contributed by processed food in rural areas is lower than that in urban areas, for the latter may be easier to access processed food than the former [42]. In recent years, urbanization has accelerated the Chinese market expansion of processed food [43], which has provided residents more opportunities to obtain processed food. Therefore, the total dietary sodium could be reduced by controlling sodium from processed food, and the department concerned should strengthen supervision over the labeling of sodium in processed food so that consumers can reasonably choose low-sodium food.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of dietary sodium contributed by processed food in rural areas is lower than that in urban areas, for the latter may be easier to access processed food than the former [42]. In recent years, urbanization has accelerated the Chinese market expansion of processed food [43], which has provided residents more opportunities to obtain processed food. Therefore, the total dietary sodium could be reduced by controlling sodium from processed food, and the department concerned should strengthen supervision over the labeling of sodium in processed food so that consumers can reasonably choose low-sodium food.…”
Section: Discussionmentioning
confidence: 99%
“…66 Public messages should be given that emphasize the harmful effects of excessive food intake and lack of physical exertion. 67 Primary care physicians can play a vital role in preventing obesity and related comorbidities by educating patients, recommending different strategies, and involving a multidisciplinary team of healthcare workers to provide effective obesity therapy and prevention to their patients. A dietician can be an integral part of this team as dieticians can aid patients in developing adoption of a balanced diet by providing healthy food education.…”
Section: Public Health Implicationsmentioning
confidence: 99%
“…Riskesdas 2007 result showed that the national prevalence of undernutrition is 13.0% and overweight is 4.3% in infants (Badan Litbangkes, 2008). However, there was a combination of diverse nutritional status in the family (Nti, 2011) (Zhang et al, 2017). This was caused by imbalanced food distribution in the family and lack of knowledge on nutrition in the family (including the mother).…”
Section: Introductionmentioning
confidence: 99%